Downstream Fish Passage Status Report. - Northeast Utilities Service Company (ScholarWorks@UMass Amherst, 1987)
None supplied. Introduction: On November 5, 1985, the Federal Energy Regulatory Commission (FERC) issued an Order Amending License for the Hadley Falls Project, FERC Project No. 2004, to add Chemical Station to the License. The amendment included Article 40, which required the Licensee, Holyoke Water Power Company (HWP), to file a status report on existing downstream fish passage facilities at the Project and to present a plan for future facilities. This report, compiled by Northeast Utilities Service Company (NUSCO), is intended to fulfill that requirement.